Diet, physical activity, and screen time among school students in Manipur - Markordor Lyngdoh; Brogen Singh Akoijam; R K S. Agui; K h Sonarjit Singh (Wolters Kluwer Medknow Publications, 2019)
Context: Adolescence is a critical time in the development of lifelong healthy eating and exercise habits. The high prevalence of adolescents exposed to excessive screen time is a matter of concern because of its association with several health problems, such as overweight and obesity, alterations in blood glucose and cholesterol, poor school performance, decreased social interaction, and lower levels of physical activity. Aims: The aim of this study is to identify the lifestyle behaviors of young adolescents focusing on physical activity, diet, and screen time. Settings and Design: A cross-sectional study was conducted among 929 students of Class VII and VIII in schools in Imphal West and Kangpokpi districts of Manipur. Subjects and Methods: Data collection was done by questionnaire method. Statistical Analysis Used: The data were analyzed using IBM SPSS for Windows, Version 21.0. Armonk, NY, USA. Results: Seven in 10 of the students had inadequate physical activity at school and inadequate physical activity outside school. About 56.9% of the students have a smartphone, whereas one-third of them have Facebook and WhatsApp accounts. Only 5.8% were eating a healthy diet. Females and day scholars were less physically active. Males those staying in a nuclear family, less family income, and more number of siblings were found to have unhealthy dietary habits. Conclusions: Less than half of the students were physically active and only six out of 100 the students were eating a healthy diet.